Trapezoidal Type Fejér Inequalities Related to Harmonically Convex Functions and Application. (4th April 2019) - Turhan, Sercan
Abstract : Some authors introduced the concepts of the harmonically arithmetic convex functions and establish some integral inequalities of Hermite Hadamard Fejér type related to the harmonically arithmetic convex functions. In this paper, a mappingM ( t ) is considered to get some preliminary results and a new trapezoidal form of Fejér inequality related to the harmonically arithmetic convex functions. By using a mappingM ( t ), the new theorems and corollaries are obtained. Taking advantage of these, applications were given for some real number averages.